2014
DOI: 10.3171/2013.9.peds131
|View full text |Cite
|
Sign up to set email alerts
|

Occipital condyle to cervical spine fixation in the pediatric population

Abstract: Fixation at the craniovertebral junction (CVJ) is necessary in a variety of pediatric clinical scenarios. Traditionally an occipital bone to cervical fusion is preformed, which requires a large amount of hardware to be placed on the occiput of a child. If a patient has previously undergone a posterior fossa decompression or requires a decompression at the time of the fusion procedure, it can be difficult to anchor a plate to the occipital bone. The authors propose a technique that can be used when face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
15
1
2
Order By: Relevance
“…A promising technique is segmental occipital condyle screw (OCS) fixation. 1,3,5,6,8,[11][12][13][14][15][16][17]21,[24][25][26][27] A few anatomical, 5,6,12,14-17, 21,26 biomechanical, 8,24,27 and clinical 1,3,6,11,13,25 studies have identified the feasibility of OCS placement for OCJ fixation. Advantages of the OCS include a decreased length of the lever arm, longer screw length, a low profile that leaves more available bony surface area for grafting, and avoidance of dramatic rod contouring.…”
mentioning
confidence: 99%
“…A promising technique is segmental occipital condyle screw (OCS) fixation. 1,3,5,6,8,[11][12][13][14][15][16][17]21,[24][25][26][27] A few anatomical, 5,6,12,14-17, 21,26 biomechanical, 8,24,27 and clinical 1,3,6,11,13,25 studies have identified the feasibility of OCS placement for OCJ fixation. Advantages of the OCS include a decreased length of the lever arm, longer screw length, a low profile that leaves more available bony surface area for grafting, and avoidance of dramatic rod contouring.…”
mentioning
confidence: 99%
“…Initially described in 2008 by La Marca et al, 15 then further investigated by Kosnik-Infinger et al 13 and Uribe and colleagues 16,17,25 via radiological and cadaveric analysis, the technique has since been shown to be a viable method to fuse the occiput and cervical spine. Specifically, it has been used in a pediatric setting of craniocervical instability from tumor surgery, craniovertebral anomalies, and prior suboccipital decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been used in a pediatric setting of craniocervical instability from tumor surgery, craniovertebral anomalies, and prior suboccipital decompression. 2,13 There are biomechanical data demonstrating that condylar screws provide stiffness in flexion, extension, and lateral and axial support equivalent to that provided with the currently available constructs for OCF. 26 The technique involves placing occipital condyle screws, usually with the aid of neuronavigation.…”
Section: Discussionmentioning
confidence: 99%
“…В последние шесть лет винтовая фиксация шейного отдела позвоночника у детей получила широкое распространение [2,6,8,10,13,16,20,23,26,29,33,35,40,42,43,47,51,53]. Использование винтовых конструкций для лечения патологии позвоночника позволяет создавать надежный каркас для дальнейшего спондилодеза [4,13,22,43], интраоперационно выполнять посегментарную редукцию смещений [13,33,41,43], избегать длительного применения гало-аппарата [4,8,9,11,13,14,18,32,43], является биомеханически надежным видом фиксации, поскольку при 3-колонной системе распределения нагрузки тела позвонков и передняя колонна несут 36 % опорной нагрузки, а задние структуры шейного отдела позвоночника берут на себя больший вес (64 %).…”
unclassified
“…КТ-морфометрия С 2 позвонка показала, что транспедикулярное проведение винтов размером от 3,5 на 14,0 мм в С 2 возможно у 40-70 % детей старше 2 лет [10,29], при этом ширина и высота ножки примерно одинаковы. В клинической практике транспедикулярная и интерартикулярная фиксация С 2 продемонстрировали надежность и безопасность при использовании у детей [8,13,14,17,23,26,27,37,43,46].…”
unclassified